395. Missed Opportunities for Diagnosis of Cryptococcal Disease in Patients From Florida. (26th November 2018) - Salazar, Ana S; Keller, Matt; Olsen, Margaret A; Powderly, William; Spec, Andrej
Abstract: Background: Cryptococcal disease (CD) often has an insidious presentation and can be difficult to recognize. However, delayed diagnosis can lead to increased morbidity and mortality. Methods: To estimate the potential number of missed opportunities for CD diagnosis we utilized the Healthcare Cost and Utilization Project State Inpatient Database from the Agency for Healthcare Research and Quality for the state of Florida from 2005 to 2014. We defined a missed opportunity as an admission with a new diagnosis of CD preceded by a hospitalization in the prior 90-days coded for an infection, respiratory, or central nervous system condition suggestive of CD. We performed descriptive statistics including mortality in each exposure group within one year after CD diagnosis. Results: We identified 1, 622 CD-related hospital discharges in Florida from April 2005 to December 2014. The median age of CD patients was 47 years, 30.6% were female, and 55.5% were coded for HIV/AIDS. Of those, 850/1, 622 (52.4%) had meningitis. Five hundred sixty (34.5%) had a prior hospitalization within 90 days before the first hospitalization coded for CD. Of those, 50.9% (285/560) had a potentially missed opportunity to diagnose CD of whom 138/285 (48.4%) were HIV-positive. Of 560 patients, 49 (8.7%) were coded during a prior hospitalization with CNS conditions, 162 (28.9%) with respiratory conditions and 74 (13.2%) coded with both CNS and respiratory conditions. Patients who were coded for CNS diagnoses in a prior admission were more likely to be diagnosed with CD meningitis ( P < 0.001). Of those with prior respiratory conditions 29/218 (13.3%) died during the CD admission, and 12.5% of those with prior CNS conditions died during the CD admission. Of those without a prior admission in the past 90 days, 110/1, 062 (10.4%) died during the CD admission. Conclusion: Cryptococcosis is a deadly disease that affects patients with both competent and incompetent immune systems. Missed opportunities to diagnose CD are relatively commonmand may contribute to worse outcomes. Disclosures: All authors: No reported disclosures.